Dietary intake, energy availability, and power in men collegiate gymnasts - Kuhlman, N. M.; Jones, M. T.; Jagim, A. R.; Magee, M. K.; Wilcox, L.; Fields, J. B. (Frontiers in Sports and Active Living, 2024)
Introduction The purpose was to examine the prevalence of low energy availability (LEA), explore dietary behaviors in men collegiate gymnasts (n = 14), and investigate the relationships between energy availability (EA), body composition, and plyometric performance.